UPAYA PENINGKATAN PEMAHAMAN IBU TENTANG PENTINGNYA IMUNISASI PADA BAYI DI DESA PAKU KEC.GALANG - Situmorang, Paskah Rina; Nataria Yanti Silaban (Jurnal Ilmiah Pengabdian Kepada Masyarakat (Ji-SOMBA), 2022)
Immunizations are mandatory for infants aged 0-9 months. Immunization is an effort made to actively induce/enhance a person's immunity against a disease so that if one day they are exposed to a disease, they will not get sick. Only experiencing mild symptoms (Permenkes RI, 2017). The purpose of immunization is to provide protection against diseases that can be prevented by immunization. In Indonesia, immunizations that are required by the government and WHO include; BCG, DPT, Hepatitis, Measles and Polio immunizations. According to data obtained from WHO data based on routine immunization data reports in October 2021, complete basic immunization coverage has only reached 58.4 persen of the target of 79.1 persen. Banten is just approaching the target of complete basic immunization coverage, which is 78.8 persen. Meanwhile, a number of complete basic immunization coverage areas are above 60 persen, including; South Sulawesi, Bengkulu, North Sumatra, Bali, Gorontalo, Bangka Belitung, East Java, Jambi. The method used is descriptive observational with 32 participants who are in Galang Village. Sample selection based on purposive sample. While the data collection through the evaluation of the question instrument carried out with a check list about the importance of immunization in infants. The community service team provided material about the importance of immunizing babies directly by complying with health protocols. From the evaluation results, it was found that there was an increase in participants' knowledge about the benefits of the importance of giving immunizations to infants from 69 persen less knowledge of mothers to 95 persen good. Knowledge is an important domain and is the initial factor for a person to behave. Knowledge forms participants' beliefs so that they want to immunize their babies.